Epithelioid trophoblastic tumor initially misinterpreted as uterine smooth muscle tumor with vaginal and sigmoid colon metastases - Basheska, Neli; Prodanova, Irina; Veljanoska-Petreska, Slavica; Kubelka-Sabit, Katerina; Jashar, Dzengis; Naumov, Janaki (Macedonian Association of Anatomists and Morphologists, 2005)
The epithelioid trophoblastic tumor (ETT) is a rare trophoblastic neoplasm with a wide spectrum of differential diagnoses and unpredictable clinical behaviour. A 43-year-old woman underwent hysterectomy for an intramural uterine nodule initially misinterpreted as smooth muscle tumor. Subsequently, 91 and 113 months later, two recurrences were discovered: at the vaginal stump and in the sigmoid colon. The histological and immunohistochemical findings of the primary and the metastatic tumors were consistent with the diagnosis of ETT. Therefore, immunohistochemistry could help in confirming the diagnosis of ETT. In these patients, subsequent to primary surgical treatment, a careful and prolonged follow-up is warranted.
Епителоиден трофобластичен тумор првично интерпретиран како мазно мускулен тумор со метастази на вагина и во сигмоиден колон
Keywords: epithelioid trophoblastic tumor; chorionic-type intermediate trophoblast; metastasis; vagina; sigmoid colon; immunohistochemistry